Answer:
[tex]height=\frac{6x^2-2x+8}{2x-4}[/tex]
Step-by-step explanation:
Given equation of volume is [tex]6x^2-2x+8[/tex]. Also given that bsae area is
[tex]2x-4[/tex].
In a rectangular prism,
[tex]volume =area of base*height[/tex]
So height would be ,
[tex]\frac{volume}{areaofbase}[/tex]
On substituting we get ,
[tex]height=\frac{6x^2-2x+8}{2x-4}[/tex]
First let us factorize [tex]6x^2-2x+8[/tex].
[tex]2(3x + 1)(x - 4)=6x^2-2x+8[/tex]
As 2x-4 is not an factor expression for height would be
[tex]height=\frac{6x^2-2x+8}{2x-4}[/tex]